Effects of an experimental short-time high-intensity warm-up on explosive muscle strength performance in soccer players: A pilot study - Antonino Patti; Valerio Giustino; Norikazu Hirose; Giuseppe Messina; Stefania Cataldi; Giuseppe Grigoli; Alida Marchese; Giuseppe Mulè; Patrik Drid; Antonio Palma; Antonino Bianco (Frontiers in Physiology, 2022)
Objective: This study aimed to evaluate the effects of an experimental short-time warm-up consisting of a small number of intermittent high-intensity sprints on explosive muscle strength performance in soccer players and to identify recovery times after performing the sprints. Furthermore, we evaluated the reliability of a smartphone app in jumping performance.Methods: Twenty male soccer players were given the following tests: 1) the counter-movement jump (CMJ) test with the Microgate system, 2) the counter-movement jump (CMJ) test with the MyJump smartphone app, and 3) the handgrip strength test. The experimental short-time high-intensity warm-up was carried out 1 week after test administration. The warm-up consisted of three maximum sprints over 60 m with 120 s of recovery between sprints. Then, the tests were administered again: the vertical jump height (VJH) performances (five trials) were measured 90 s after the last sprint; the handgrip strength performances (three trials) were measured 120 s after the last vertical jump test.Results: The maximum VJH was found in the third trial of the CMJ test, 330 s after the last sprint (p < 0.01), the result closest to the baseline. The lowest VJH was found in the first trial of the CMJ test, 90 s after the last sprint (p < 0.05). Pearson’s analysis between the CMJ test with the Microgate system and the CMJ test with MyJump showed a strong correlation (R = 0.96). Lin’s concordance correlation coefficient showed a substantial concordance (ρc = 0.959) between measures.Conclusion: This experimental short-time warm-up of high-intensity intermittent sprints appears to be a simple, quick, and efficient activity to accelerate soccer players’ optimal performance.